PERSEPSI SISWA TERHADAP PENERAPAN PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA PADA MATERI SPLDV - Dwi Susanti; Husni Sabil; Bella Arisha (De Fermat : Jurnal Pendidikan Matematika, 2026)
Problem Based Learning is a learning model that focuses on contextual problem solving to help students understand concepts in a more meaningful way. In its implementation, PBL can be combined with ethnomathematics by linking learning materials to cultural contexts, so that the problems presented become closer to students’ experiences. This study aims to examine students’ perceptions and identify the factors that influence them in the SPLDV material. This study uses a qualitative approach with 30 eighth-grade students of SMP Negeri 22 Sarolangun as the subjects. Data were collected through questionnaires, interviews, and observations. The results of the study show that students’ perceptions of learning are in the high, medium, and low categories based on the questionnaire results. This shows that students’ perceptions vary among individuals. Learning that is linked to cultural contexts can help students’ understanding and increase their interest and engagement, but it has not been felt evenly by all students. These perceptions are influenced by internal factors, such as attention, motivation, experience and prior knowledge, attitudes, and self-confidence, as well as external factors which include the characteristics of learning and the social, cultural, and physical environment. Thus, students’ perceptions are formed through the interaction of various factors in learning experiences